Agricultural innovations during economic transformation: Insights from SPIA country studies - Stevenson, James R. (2025)
This brief shows Phase 1 if SPIA country studies (Uganda, Ethiopia, Bangladesh, Viet Nam) in the process of structural transformation using the de Janvry and Sadoulet (2020) framework.